2022
DOI: 10.3389/fgene.2022.842584
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters of White Striping and Meat Quality Traits Indicative of Pale, Soft, Exudative Meat in Turkeys (Meleagris gallopavo)

Abstract: Due to the increasing prevalence of growth-related myopathies and abnormalities in turkey meat, the ability to include meat quality traits in poultry breeding strategies is an issue of key importance. In the present study, genetic parameters for meat quality traits and their correlations with body weight and meat yield were estimated using a population of purebred male turkeys. Information on live body, breast, thigh, and drum weights, breast meat yield, feed conversion ratio, breast lightness (L*), redness (a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Heritability estimates for the feather traits are presented in Table 1 . Heritability estimates for the studied growth and efficiency, carcass, and meat quality traits can be found in Vanderhout et al 41 . The reported heritability estimates in this study are from the univariate models for each trait.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heritability estimates for the feather traits are presented in Table 1 . Heritability estimates for the studied growth and efficiency, carcass, and meat quality traits can be found in Vanderhout et al 41 . The reported heritability estimates in this study are from the univariate models for each trait.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, meat pH would not decrease as much 51 explaining the positive correlation between FCORT and ultimate pH. This relationship could be a desirable consequence of selection for higher FCORT as it may help reduce the prevalence quality defects such as pale, soft, and exudative (PSE) meat 41,[53][54][55] which is associated with low meat pH. The correlation between FCORT and ultimate pH may also be influenced by the negative relationship between FCORT and breast yield where larger breast yield is associated with decreased pH and water-holding capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevation of glycolysis and pyruvate metabolism result in the accumulation of lactic acid, which consequently reduces the pH value of the postmortem meat ( Vanderhout et al, 2022 ). As the process of protein folding is critical to the proper functioning of the muscle protein, any disruptions in this process can lead to misfolded structures that may impact the quality of meat, for example, a rapid and extensive pH decline increases the denatured muscle proteins and impairs the functionality of meat ( Stajkovic et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher pH is beneficial for liquid retention (Huff- Lonergan and Lonergan, 2005). Several authors have reported an increase in the pH of pale, soft, exudative (PSE) poultry meat (Vanderhout et al, 2022) and uncured dry-fermented beef (Wójciak et al, 2019) after ultrasound treatment. Ultrasound cavitation may lead to the release of proteolytic enzymes and deaminase, increasing the availability of amino acids and basic amines (Huang et al, 2017) and reducing acidic protein groups (Amiri et al, 2018).…”
Section: Ph Whc and Texture Profile Analysismentioning
confidence: 99%